2013
DOI: 10.7314/apjcp.2013.14.9.5225
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum IL-17A but not IL-6 in Glioma Versus Meningioma and Schwannoma

Abstract: Background: There is a Th1/Th2 cytokine imbalance and expression of IL-17 in patients with brain tumours. We aimed to compare the levels of IL-17A and IL-6 in sera of glioma, meningioma and schwannoma patients as well as in healthy individuals. Materials and Methods: IL-17A and IL-6 levels were measured in sera of 38 glioma, 24 meningioma and 18 schwannoma patients for comparison with 26 healthy controls by commercial ELISA assays. Results: We observed an increase in the IL-17A in 30% of glioma patients while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Moreover, Th17-related cytokines are expressed in glioma tissues, suggesting the role of these cells in glioma tumorigenesis and progression [47, 48]. Furthermore, the serum levels of IL-17 correlate with the disease, with age [49], and with the medium conditions of glioma cells that induce Th17 cell differentiation [47], thus supporting the role of Th17 cells in glioma.…”
Section: Th17 Cells In Autoimmune and Infectious Diseasesmentioning
confidence: 99%
“…Moreover, Th17-related cytokines are expressed in glioma tissues, suggesting the role of these cells in glioma tumorigenesis and progression [47, 48]. Furthermore, the serum levels of IL-17 correlate with the disease, with age [49], and with the medium conditions of glioma cells that induce Th17 cell differentiation [47], thus supporting the role of Th17 cells in glioma.…”
Section: Th17 Cells In Autoimmune and Infectious Diseasesmentioning
confidence: 99%
“…In our hands and by testing more than 279 healthy individuals of different ages and genders, IL-17A is not elevated in general population [Supplementary Fig. 1 [40,41]. However, it remains to be identified if IL-17A increases in the sera of patients with non-malignant ovarian conditions.…”
Section: Discussionmentioning
confidence: 83%
“…IL-17A is produced by a novel lineage of CD4+CD8+ T helper cells, namely TH17 cells (Moseley et al, 2003;Harrington et al, 2005;Bettelli et al, 2006), participating in both innate and adaptive immune responses. Several researches have found that high expression of IL-17A was associated with various tumor tissues, including gastric cancer, breast cancer, ovarian cancer, multiple myeloma, colorectal cancer and glioma (Kato et al, 2001;Alexandrakis et al, 2006;Zhang et al, 2008;Zhu et al, 2008;Doroudchi et al, 2013;Straus, 2013). IL-17A plays a pro-inflammatory role by recruiting neutrophils and inducing other inflammatory molecules, such as interleukin-1 (IL-1) or tumor necrosis factor-α (TNF-α) (Moseley et al, 2003;Kolls and Linden, 2004).…”
Section: Introductionmentioning
confidence: 99%